Reexamination of the Radial Abundance Gradient Break in NGC 3359 - Zahid, H. Jabran (2011)
In this contribution, we reexamine the radial oxygen abundance gradient in the strongly barred spiral galaxy NGC 3359, for which, using an imaging spectrophotometric technique, Martin & Roy detected a break near the effective radius of the galaxy. We have new emission line flux measurements of H II regions in NGC 3359 from spectra obtained with the Subaru telescope to further investigate this claim. We find that there are small systematic variations in the line ratios determined from narrowband imaging as compared to our spectroscopic measurements. We derive and apply a correction to the line ratios found by Martin & Roy and statistically examine the validity of the gradient break proposed for NGC 3359 using recently developed metallicity diagnostics. We find that, with a high degree of confidence, a model with a break fits the data significantly better than one without it. This suggests that the presence of a strong bar in spiral galaxies can generate measurable changes in the radial distribution of metals.